2019
DOI: 10.3390/v11080690
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Phylogenetic Characterization of Human Enteroviruses Isolated from Cases of Aseptic Meningitis in Brazil, 2013–2017

Abstract: Aseptic meningitis is a common viral infection associated with human enteroviruses. The aim of the present study was to identify and characterize the enteroviruses associated with outbreaks and sporadic cases of aseptic meningitis that occurred in different regions of Brazil between 2013 and 2017. Cerebrospinal fluids obtained from patients admitted to public health facilities were analyzed. A total of 303 patients were positive for Human Enteroviruses (EV) by cell culture isolation with a median isolation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 33 publications
11
50
2
Order By: Relevance
“…According to previous studies, E6 and E11 have been the most commonly detected EV types, especially among patients showing severe central nervous system syndromes [16,30,33,[42][43][44]. In this investigation, EV-A71 was the main pathogen associated with AFP (7.6%), followed by E6 (7.3%) and E11 (6.7%) suggesting a high occurrence of these types from 2005 to 2017.…”
Section: Discussionsupporting
confidence: 49%
“…According to previous studies, E6 and E11 have been the most commonly detected EV types, especially among patients showing severe central nervous system syndromes [16,30,33,[42][43][44]. In this investigation, EV-A71 was the main pathogen associated with AFP (7.6%), followed by E6 (7.3%) and E11 (6.7%) suggesting a high occurrence of these types from 2005 to 2017.…”
Section: Discussionsupporting
confidence: 49%
“…Serotype CNS symptoms References Huang Y. et al, 2015;Mao et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Ramalho et al, 2019 EV CV-A16 E/M/AFP Goto et al, 2009;Xu et al, 2012;Huang Y. et al, 2015;Holmes et al, 2016;Suresh et al, 2018 B CV-A9 E/M/AFP Holmes et al, 2016;Chen et al, 2017;B'Krong et al, 2018;Suresh et al, 2018;Ramalho et al, 2019;Sun et al, 2019 CV-B1 E/M/AFP Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019;Sun et al, 2019 CV-B2 E/M/AFP Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019 CV-B3 E/M/AFP Holmes et al, 2016;Mao et al, 2016;Mao et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019;Sun et al, 2019 CV-B4 E/M/AFP Holmes et al, 2016;Mao et al, 2016;B'Krong et al, 2018;Mao et al, 2018;Suresh et al, 2018;Sun et al, 2019 CV-B5 E/M/AFP Holmes et al, 2016;Mao et al, 2016;Chen et al, 2017;…”
Section: Speciesmentioning
confidence: 99%
“…Non-polio enteroviruses are also known to infect the CNS and account for the majority of recent enteroviral infections with neurological disorders. Among the non-polio enteroviruses, the species Enterovirus A like enterovirus 71 (EV-A71), coxsackievirus A6 (CV-A6), and CV-A16 (Goto et al, 2009;Xu et al, 2012;Huang Y. et al, 2015;Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018), the species Enterovirus B like CV-B1 (Sun et al, 2019), CV-B3 (Fan and Liu, 2019), CV-B5 (Mao et al, 2018), CV-A9, Echovirus 6 (E-6), E-7, E-11, and E-13 (Holmes et al, 2016;Chen et al, 2017;B'Krong et al, 2018;Suresh et al, 2018;Chen et al, 2019;Ramalho et al, 2019;Sun et al, 2019), the species Enterovirus C like CV-A24 (Tapparel et al, 2013;B'Krong et al, 2018;Suresh et al, 2018), and the species Enterovirus D like EV-D68 (Tapparel et al, 2013;Messacar et al, 2018) have been shown to involve the CNS and cause diverse neurological complications such as encephalitis, meningitis and acute flaccid paralysis (AFP) (Tapparel et al, 2013) (see Table 1 for details).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFP is not a single disease type, but a group of syndromes characterized by an acute onset, decreased muscle tone, decreased muscle strength, and reduction or complete loss of tendon reflexes. Poliovirus is one of the major causes of AFP and belongs to EV-C [18,19]. Children are prone to acute paralysis syndrome mainly because the neuro-immune system of infants and young children is not yet mature; their immune function is weak and susceptible to viral infection, and their nervous system is still developing.…”
Section: Introductionmentioning
confidence: 99%